Effect of Waste Tire Rubber on the Durability Behavior of Cement Composites: A Review - Isyaka Abdulkadir; Bashar S. Mohammed (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
A lot of literature reviews exist on the mechanical properties of rubberized cement composites (mortar, concrete and engineered cementitious composite). However, very little of such works exist on the effect of waste tire rubber on the durability of the composites. This paper aims to review how the use of tire rubber in cement composites affects the water absorption, permeability and resistance to aggressive chemicals (sulphates and chlorides). Recent literatures on the use of CR in concrete, mortar, and Engineered Cementitious Composites (ECC) were reviewed to assess how incorporation of rubber influences the water absorption, permeability, and chloride and sulphate resistance of the composites. The findings revealed that CR incorporation consistently enhances the resistance of the composites to the adverse effect of chloride and sulphate ions. However, there are differing opinions by researchers regarding the effect of the CR on water absorption and permeability of the rubberized composites.